SD quants—Sensitive detection tetraplex-system for nuclear and mitochondrial DNA quantification and degradation inference. (September 2019) - Xavier, Catarina; Eduardoff, Mayra; Strobl, Christina; Parson, Walther
Highlights: New real time qPCR method for nuclear and mitochondrial DNA quantitation. Two different-sized mtDNA targets enable DNA degradation inference. Internal Positive Control allows the detection of inhibitors. Abstract: Measuring the quantity of DNA present in a forensic sample is relevant in a number of ways. First, it informs the analyst about the general DNA content to adjust the volume of DNA extract used for the genotyping assay to the optimal conditions (when possible). Second, quantification values can serve as plausibility checks for the performance of the DNA extraction method used as extraction positive and negative controls demand expected values. Third and relevant to highly compromised specimens, DNA quantification can inform about the degradation state of the DNA extracted from the unknown biological sample and aid the choice of downstream genotyping assays. While there are different, commercial products for the quantification of nuclear DNA available, commercial mitochondrial DNA (mtDNA) quantification systems are rare. Even more so, the simultaneous quantification of nuclear and mtDNA that is of relevance in highly degraded forensic specimens has rarely been described. We present here a novel real-time qPCR based tetraplex system termed SD quants that targets two different-sized mtDNA and a nuclear DNA region and includes an internal positive control to monitor potential inhibition. SD quants was compared to other existing quantification systems and subjected to analysis of severely degraded DNA present in ancient DNA and aged forensic specimens. This study complies with the MIQE (Bustin et al., 2009) guidelines (when applicable).